The Role of Data Science in Modern Economic Forecasting - Karimov, Dr. Ibrokhim (Journal of Science & Technology, 2021)
This article examines how data science, through machine learning (ML) and artificial intelligence (AI), is revolutionizing economic forecasting. Traditional econometric models, often linear and simplistic, fail to capture complex economic dynamics. Data science, by leveraging vast datasets and advanced algorithms, offers more accurate forecasts for critical indicators such as inflation, unemployment rates, and GDP growth. This paper highlights key use cases of AI-driven models and discusses how they are transforming economic analysis and decision-making.
Keywords: Data Science; Economic Forecasting; Machine Learning; Artificial Intelligence; Predictive Modeling